2015
DOI: 10.3233/ves-150540
|View full text |Cite
|
Sign up to set email alerts
|

Influences of monocular and binocular vision on postural stability

Abstract: To compare the influences of monocular vision versus binocular vision on postural control, twenty-seven otherwise healthy adults, aged from 19 to 38 years, with corrected visual acuity of better than or equal to 20/20, were recruited. Body sway for standing 30 seconds on a force platform in 3 conditions was recorded for each participant: one with both eyes open (BEO), one with left eye open (LEO) and the other with both eyes closed (BEC). Postural stability was subsequently evaluated by measuring the total tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
(21 reference statements)
2
10
0
Order By: Relevance
“…There was little evidence for binocular inhibition when the monocular acuity in the two eyes were unequal. 9 This research suggested that binocular acuity and the better eye monocular acuity had a high correlation (r=0.920, P<0.001); both of them could evaluate reading acuity (r=0.827, P<0.001; r=0.862, P <0.001), binocular acuity exhibited higher correlation than monocular acuity in the better eye.Also, there were differences between monocular acuity in the better eye and binocular acuity (Z=-23.025, P<0.05) at the level of a=0.05. For a significant portion of this elderly population, binocular performance was not well represented by better eye monocular measures.…”
Section: Discussionmentioning
confidence: 71%
“…There was little evidence for binocular inhibition when the monocular acuity in the two eyes were unequal. 9 This research suggested that binocular acuity and the better eye monocular acuity had a high correlation (r=0.920, P<0.001); both of them could evaluate reading acuity (r=0.827, P<0.001; r=0.862, P <0.001), binocular acuity exhibited higher correlation than monocular acuity in the better eye.Also, there were differences between monocular acuity in the better eye and binocular acuity (Z=-23.025, P<0.05) at the level of a=0.05. For a significant portion of this elderly population, binocular performance was not well represented by better eye monocular measures.…”
Section: Discussionmentioning
confidence: 71%
“…Binocular vision disorders can generate postural adaptations to maintain binocularity and achieve visual comfort. In a literature review, we found authors who affirmed the influence that binocular vision has on posture [16,37,[42][43][44][45][46]. Prior research concluded that convergence seems to significantly enhance postural stability [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies did not investigate the effect of visual acuity in the worse eye. Wu et al compared the posture stability by measuring the total track length and surface area of center of pressure of body sway between with one eye close or both eye open, and reported that one eye close significantly increase the posture instability [ 25 ]. These results suggest that worse BCVA in the worse eye increase posture sway, may result in increased risk of falling.…”
Section: Discussionmentioning
confidence: 99%
“…Coleman et al reported that subjects with history of frequent falling is five times more likely to experience multiple fall in a large sample prospective study [ 24 ]. In the Salisbury eye evaluation, subjects with history of falls is two times more likely to fall in a population based prospective study [ 25 ]. In agreement with these studies, our current study suggested that previous history of falls was a risk factor for future fall in subjects with POAG.…”
Section: Discussionmentioning
confidence: 99%